PENGEMBANGAN MODUL BERBASIS DISCOVERY LEARNING PADA KONSEP USAHA DAN ENERGI BERORIENTASI LITERASI SAINS - Ambatoding, Dewiyanti; Budiarti, Indah Slamet; Triwiyono (Papua Journal of Physics Education, 2023)
This study aims to develop a product in the form of a Discovery Learning-based teaching module to improve the scientific literacy skills of students at SMA N 1 Sentani, Kab. Jayapura. In this study using research and development (Research and Development) which refers to the Borg and Gall development model according to (Borg and Gall, 2003) the steps that should be taken in research development (Research and Development) include: (1) research and information collection (research and data collection), (2) Planning (planning), (3) Develop premilinary form of product (developing initial product/product draft),(4) preliminary field testing (initial field trials However, the research model and Borg and Gall development was only carried out by researchers until the fourth stage) because the purpose of this research was only to develop and produce validand feasible products. Based on research data obtained from research and development idi is teaching materials in the form of teaching modules produced and developed by Borg and Gall. The validation of the feasibility of the High School Physics module on Business and Energy Materials Based on Discovery Learning by one expert lecturer and physics teacher got an overall percentage of 83% with a very good interpretation so that it is feasible to be used in the learning process.